Characterization of endoplasmic reticulum targeting liposomes as drug delivery vesicles - Skelton, K (2012)
Due to rapid viral and drug resistance mutations, there is a great need for broad-spectrum antiviral therapies that target the host rather than viral processes. This research builds upon previous studies developing α-glucosidase inhibitors known as iminosugars as broad-spectrum antiviral drugs. Initially pH-sensitive liposomes were designed and developed as drug delivery vehicles to enhance cellular internalization for α-glucosidase inhibitors for HIV-1 antiviral treatment. Recent studies by Pollock et al. have shown that polyunsaturated endoplasmic reticulum targeting liposomes known as PERLs, traffic to the ER and are antiviral as a stand-alone therapy against hepatitis B, hepatitis C, and HIV. In addition, α-glucosidase inhibitors formulated and delivered by 'ER-targeting' liposomes have shown potential in recent preclinical studies in vitro and are candidates for future clinical trials as antiviral treatments. There are two main purposes of this research. Firstly, it aims to develop crucial quantitative analytical methods that detect the α-glucosidase inhibitor drugs when formulated in 'ER-targeting' liposomes. The analytical methods will help elucidate how the chemical properties of small molecules, such as hydrophobicity or polarity, affect the encapsulation efficiency into 'ER-targeting' liposomes, which will help select appropriate formulation processes and dosing regimes for potential future clinical trials. Secondly, this research intends to dissect the possible cellular internalization and trafficking pathways that the 'ER-targeting' liposomes, such as PERLs, utilize to get to the ER in vitro. A large screening assay was conducted to determine what influence each type of phospholipid has on the cellular entry and intracellular movement of 'ER-targeting' liposomes. Several key observations were drawn from this research that will hopefully further the knowledge of 'ER-targeting' liposomes' capability to deliver iminosugars and the pathways involved with the cellular internalization and trafficking of the liposomes in vitro.